Coaching Assessment System (CAS-V2) / Nursaadatun Nisak Ahmad ... [et al.] - Ahmad, Nursaadatun Nisak; Ismail, Ida Rosnita; Ismail, Azman; Aliman, Nor Khasimah; Tuan Kub, Mohd Nor Hafiz; Mohd Salim, Nor Zarina (2020)
Management Coaching Role is the management's coaching style that links the role of immediate superiors and employees in an organisation. Findings of a recently conducted study highlight that the relationship between coaching style is able to influence employees' behaviour. This is in line with the government's aspiration, as illustrated in the fifth pillar of 10th Malaysia Plan (10MP), that clarifies the importance of quality human capital can contribute to the improvement of country's economics and productivity. The third pillar in the Human Resource Development Strategic Plan (PSKSM 2016-2020) also clarifies the importance of managing quality employees through coaching method for the purpose of improving work performance. Furthermore, the SmartPLS method was used to evaluate the validity and reliability of the study questionnaire. The results show, role of immediate superiors in coaching employees is highly required as they are the closest individuals to the employees.Therefore, this Coaching Assessment System (CAS) is introduced to assess the coaching practice carried out by immediate superiors with their supervised employeesin the public service sector. The system also able to assist the organization in improving tasks effectiveness and employees' performance through the enhancement of management role in coaching employees at the workplace.